“Estudio de la rentabilidad económica para la planificación de la inversión de los talleres artesanales del barrio de los carpinteros, cantón Riobamba, período 2013-2015.” - Hervas Guerrero, María Fernanda (2017)
The profitability economic return obtained by a company represents the result of the activity carried out during a given period. At the artisanal level, it is difficult to accurately calculate the profitability especially if the operations are not recorded or omitted data that are so necessary to know the volume of sales and the costs and expenses generated. The objective of the research was to determine the impact of the study of the economic profitability in the planning of the investment of the craft workshops of the Barrio de los Carpinteros, canton Riobamba, period 2013-2015. Similar studies and the contributions of several authors of the financial area were taken as theoretical basis. The methodology exposes the method used, in this case the hypothetical inductive being its type of documentary and field character, the design was non-experimental and its descriptive level. The techniques of information collection were the survey and observation and as instruments the questionnaire and the observation guide, applied to the population integrated by the owners of the craft workshops. The results show that the economic profitability of craft workshops did not affect investment planning during the investigation period, except for investing in the acquisition of raw materials.